Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Genetic homogeneity of krill (Euphausia superba Dana) in the Southern Ocean - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1989)
Development of a comprehensive picture of the genetic population structure of the Antarctic krill (Euphausia superba) has been hampered by a lack of genetic data from two major areas of the species' distribution, the Bellingshausen Sea and the Ross Sea. Evidence from earlier studies of a discrete “Bellingshausen Sea” population was based on anomalous allele frequencies in two sample sets that were collected near the west coast of the Antarctic Peninsula rather than in the Bellingshausen Sea proper. In this paper we describe the first biochemical genetic data obtained on krill from the central Bellingshausen Sea and from the Ross Sea. Analyses of eight polymorphic loci in samples from these two areas have failed to provide any evidence of population structuring within the Pacific sector of the Southern Ocean, and have indicated that Pacific sector krill cannot be genetically discriminated from Atlantic sector krill or Indian Ocean sector krill. These findings further support the hypothesis of a single circumpolar breeding population of Antarctic krill.
Keywords: Rosshavet; Sørishavet; biokjemi; genetikk; krill; marin biologi; plankton

Phytoplankton blooms in the vicinity of palmer station, Antarctica - Holm-Hansen, Osmund; Mitchell, Brian Gregory; Hewes, Christopher D; Karl, David Michael (Polar Biology, 1989)
Fifteen oceanographic stations were occupied in the vicinity of Anvers Island, Antarctica, in January of 1985 and 1987. All stations showed high phytoplankton biomass (4.0 to 30 μg chl-a/liter) which was either uniformly distributed in the upper mixed layer or showed a pronounced sub-surface maximum at 4–5 m depth. As phosphate was less than 0.02 μm and nitrate about 2.0 μm in surface waters, it appears that nutrient limitation of phytoplankton growth may be of importance during such blooms. This view is supported by chemical measurements of the particulate material which showed high chl-a/ATP ratios (about 7.7), as well as high POC/ATP ratios (about 700). Microscopical analysis revealed a dominance of large-celled diatoms and the near absence of heterotrophic protozoans. Size fractionation studies showed that the nanoplankton accounted for only 28% of the total phytoplankton biomass. When phytoplankton biomass reaches the levels found at these stations, it appears that the cells are light-limited and hence dark-adapted, which results in the high chl-a/ATP ratios and the low assimilation values (0.49–1.64) obtained in our studies. Under such conditions greater than 50% of the total phytoplankton biomass is found below the 1% light level.
Keywords: Sørishavet; biomasse; fytoplankton; oseanografi

En hvalfangstsesong med mange forlis. Den første "Kosmos" - Møller, Vilhelm (Kjære gamle Sandefjord, 1989)
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangstindustri; hvalindustri

Storrederiet Nortraship : handelsflåten i krig - Mossige, Erling (Grøndahl, 1989)
Keywords: Norge; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk; rederier; skipsfart

Hjelpekrysser kaprer norske hvalfangere - Nilsen, Tore L.; Thowsen, Atle (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1989)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Sørishavet; andre verdenskrig; historie; hvalbåter; hvalfangstflåten; pelagisk

Life at the Ice Edge - Sakshaug, Egil; Skjoldal, Hein Rune (Ambio, 1989)
Publisher: [Springer, Royal Swedish Academy of Sciences]
Keywords: Sørishavet; alger; forurensning; fytoplankton; krill; miljø; planteplankton; zooplankton